Thus L.H.S = R.H.S that is 2/√3cosx + sinx = sec(Π/6-x) is proved
We have to prove that
2/√3cosx + sinx = sec(Π/6-x)
To prove this we will solve the right-hand side of the equation which is
R.H.S = sec(Π/6-x)
= 1/cos(Π/6-x)
[As secƟ = 1/cosƟ)
= 1/[cos Π/6cosx + sin Π/6sinx]
[As cos (X-Y) = cosXcosY + sinXsinY , which is a trigonometry identity where X = Π/6 and Y = x]
= 1/[√3/2cosx + 1/2sinx]
= 1/(√3cosx + sinx]/2
= 2/√3cosx + sinx
R.H.S = L.H.S
Hence 2/√3cosx + sinx = sec(Π/6-x) is proved
Learn more about trigonometry here : brainly.com/question/7331447
#SPJ9
Answer:
6cm is the missing length
Step-by-step explanation:
See the 10cm and the 4cm?
If you look at in a way if you added 6 more centimeters to the 4cm it would be 10, leaving 6cm as the missing length.
Answer:
Step-by-step explanation:
In order to find the value of n that satisfies this equation, we can perform a series of algebraic steps on it to solve for n.
-
- <em>Distribute in the 8 on the left side:</em>
- <em /><em> </em>
- <em>Add 4n to both sides</em>
-
- <em>Add 16 to both sides</em>
-
- <em>Divide both sides by 20</em>
-
Therefore, n=1 is the value of n that satisfies this equation.
Hope this helped!